Research on Path Planning and Trajectory Generation of Hoists for Lifting Sluice Gates - Hou Chunyao; Fang Zifan; Zhou Yi; Zhang Yu; Dong Yuanfa (Jixie chuandong)
In order to solve the problems of the frequent lifting sluice gates, the high intensity and the low efficiency of hoists in hydropower stations, a method of path planning and trajectory generation of hoists suitable for the unmanned automation was proposed. Aiming at the basic problems of the loading and unloading sequence and the path planning of hoist lifting gates, the analysis model of lifting operations was established, the working space of the hoist and the movement direction of the three mechanisms of lift, trolley and gantry were defined, and the initial position and unloading position database of the gates were constructed. According to the loading and unloading sequence of the gates and considering the operating environment factors, the operation path planning of the lifting gates was carried out. Considering the gate swing, the underactuated coupling relation between the gate swing and the trolley acceleration was analyzed based on the phase plane, the motion parameters were determined, and the desired trajectory of the trolley was generated. In view of the phenomena such as the groove interference and the slot jamming, a stepwise deceleration planning method for the gate falling process was proposed. The simulation and test results show that the hoist completes the lifting gates operation according to the expected plan, and the swing angle of the gate swings within a reasonable range. The method is suitable for the unmanned automatic operation environment of the hoist of hydropower stations and lays a theoretical foundation for the realization of the intelligence of hoists.